Measuring progress in precision oncology - Horak, Peter; Fröhling, Stefan (Cancer discovery, 2024)
In this issue of Cancer Discovery, Suehnholz and colleagues describe their efforts to quantify the gradual yet steady progress of precision oncology by surveying the regulatory approvals of targeted cancer therapies, and thus the actionability of corresponding molecular alterations in clinical practice, over more than 20 years. Their work also suggests a relationship between the discovery of candidate therapeutic targets through comprehensive tumor profiling and molecularly guided cancer drug development.See related article by Suehnholz et al., p. 49 (5).
Gesehen am 11.11.2024